THE QUEST FOR FINANCIAL PERFORMANCE METRIC HAVING SUPERIOR ASSOCIATION WITH SHARE PRICE - Vora, Dr. Khushboo (The journal of contemporary issues in business and government, 2022)
The purpose of this paper is to rank various performance measures in terms of information content and determine the best financial performance metric among the set of performance measures in explaining the variation in share price. For better exposition, a sample of 365 Indian listed companies, for a period of 5 years 2016-2020, have been divided into three sectors-manufacturing, financial services and non-financial services. After performing univariate regression analysis, the results of the study reveal that Earnings per share has a superior association with share price across all companies. Dividend payout ratio, long term debt to equity ratio, current ratio, fixed asset turnover ratio, debtor turnover ratio, interest coverage ratio and EBIT margin have a non-significant relationship with share price throughout the study period.